2017
DOI: 10.1103/physrevd.95.034040
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic effects in model calculations of double parton distribution functions

Abstract: In this paper we consider double parton distribution functions (dPDFs) which are the main non perturbative ingredients appearing in the double parton scattering cross section formula in hadronic collisions. By using recent calculation of dPDFs by means of constituent quark models within the so called Light-Front approach, we investigate the role of relativistic effects on dPDFs. We find, in particular, that the so called Melosh operators, which allow to properly convert the LF spin into the canonical one and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 48 publications
3
59
0
Order By: Relevance
“…It is worth mentioning that dPDF calculations within hadronic models show, in general, a breaking of the factorized ansatz, Eq. (6), in a specific region of phase space, where sizable longitudinal and mixed longitudinal-transverse partonic correlations do appear [5][6][7][8][9]. Nevertheless, in this paper we still the use the approximation in Eq.…”
Section: σ Eff and Partonic Distancesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that dPDF calculations within hadronic models show, in general, a breaking of the factorized ansatz, Eq. (6), in a specific region of phase space, where sizable longitudinal and mixed longitudinal-transverse partonic correlations do appear [5][6][7][8][9]. Nevertheless, in this paper we still the use the approximation in Eq.…”
Section: σ Eff and Partonic Distancesmentioning
confidence: 99%
“…However, our result does depend weakly on the details of fðk ⊥ Þ, since just the general conditions in Eq. (9) and its limiting asymptotics at large k ⊥ are assumed, leaving the detailed shape fðk ⊥ Þ largely unconstrained.…”
Section: B a Maximum For The Allowed Partonic Distancementioning
confidence: 99%
See 1 more Smart Citation
“…In the last part of the paper, we focus on relativistic effects in dPDF model calculations, in the relevant kinematic conditions of collider experiments, and already addressed in Ref. [12] for valence quarks at the hadronic scale. The aim of this part of the analysis is to offer insight to unfactorized ansatz for dPDFs as induced by the implementation of relativistic effects in dPDFs calculation via Melosh operators.…”
Section: Introductionmentioning
confidence: 99%
“…The two partons can be correlated either kinematically or through their quantum numbers, for recent reviews we refer to [36,37] and references therein. Model calculations of DPDFs suggest that such correlations can be large, at least at large values of x [38][39][40][41][42][43][44][45]; however, evolution to large scales tends to decrease their importance, especially at low x [26,46]. It was recently demonstrated that spin correlations can have a measurable impact on differential distributions in at least one process (same-sign W W production) at the LHC [47].…”
Section: Correlations In Dpsmentioning
confidence: 99%